Alexandra Nickerson, The Privacy Paradox: The Liberation and Burden of Being Let Alone (AmeriQuests, 2019)
Privacy is as complex a concept as it is ubiquitous. But Vanderbilt law and history professor Sarah Igo bravely takes on the challenge of chronicling the history of this mutable, yet fundamental American value. In doing so, she demonstrates the irreconcilable trade-off between privacy and exposure, both of which can be liberating and oppressive in their own right. Readers will be impressed by the depth and the breadth of this tome, as Igo examines privacy’s role in fields as disparate as law, psychometrics, philosophy, and technology. As a result, they will come away with a profound, new consciousness of being “known” to the government and to all facets of society. Despite the feelings of vulnerability this awareness may induce, Igo’s book gives us the knowledge, perspective, and foresight to revisit our own privacy debates with agency and determination. As known citizens, the future of privacy is in our hands.